Assessment of Serum IL-2 and Immunohistochemistry Detection of IL-2 in Induced Hypothyroidism of Male Rats - Abbas Abed Sharhan (Journal of Global Pharma Technology, 2018)
This study was conducted to demonstrate the role of methanolic extract from Ficuscarica leaves in the treatment of   hypothyroidism disease which induced in male rats by carbimazole drug. Forty male rats were divided into five groups, eight for each. group I selected as a negative control  which primed orally with normal saline alone, group II served as a positive control and treated by carbimazole anti-thyroid  drug for six weeks ,while  group  III  was treated by plant extract ( 500 mg /kg, bw) for six weeks ,whereas the  fourth group IV was treated by carbimazole drug (5 mg) for six weeks to induce hypothyroidism   and then  treated by plant extract ( 500 mg /kg , bw)  for six weeks too. Finally the fifth V group was  treated by thyroxin drug (100 mg) for six week instead of plant extract.The results showed that a non- significant difference (P< 0.05) in the level of  IL-2 of  the fourth  group when compared  with the first group  , while the results revealed a significant increase when compared with the  second  group  ,whereas a significance decrease when compared with the third and fifth groups. The immunohistochemical sections of  rats thyroid gland  in the first , second and third groups revealed that weak expression of IL-2 immunopositive cells (brown cytoplasmic deposits) in thyroid sections, while rats thyroid gland in the fourth group  and fifth groups revealed that a moderate expression of  IL-2 immunopositive cells. In conclusion it is possible to use methanolic extract of Ficuscarica leaves in the regulation of immune response in hypothyroidism disease may due to the presence of phytochemical components that enhance the cellular immune response by increase the IL-2 production.                                                                                     Keywords: Hypothyroidism, Carbimazole IL-2, Immunohistochemistry, Ficuscarica, phytochemical components.